A new species of Synagapetus from Spain with a key for the identification of the Iberian and Pyrenean species (Trichoptera: Glossosomatidae) - Martínez, J.; Martín, L.; González, M.a. (Zootaxa, 2015)
A new species of the caddisfly genus Synagapetus from central Spain is described and figured: Synagapetus vettonicus sp. n. Males of the new species are close to S. placidus and S. marlierorum, but the new species is well characterized by a combination of genitalic characteristics, especially those concerning the shape of the superior and inferior appendages. Additionally we provide a taxonomic key to the Iberian and Pyrenean species, in order to make the identification of this complex group of species easier.